(untitled) (CIPEEX, 2025)
This study aimed to compare the quality of cardiopulmonary resuscitation (CPR) between the lay population and healthcare students. Cardiorespiratory arrest (CRA) compromises cellular metabolism and requires a rapid response to increase the chances of survival. Using the Resusci Anne QCPR manikin and computational analysis techniques, the research evaluated 30 laypeople and 32 students from Unievangélica, demonstrating that the students obtained better results, with an average score of 82.5, while the laypeople scored 52.5 (p = 0.0006). The success rate was higher among students (72.5%) compared to laypeople (31.25%), and the time to initiate CPR was significantly shorter for students (32.5 seconds). The research reinforces the importance of formal training, such as BLS and ACLS, and continuous practice in controlled environments to improve performance and increase survival chances. Despite limitations, such as manikin simulation, the study highlights the need for training programs and better training guidelines for the population.